FAO, the first 40 years - Food and Agriculture Organization of the United Nations (Rome : Food and Agriculture Organization of the United Nations, 1985)
The book is on the anniversary of FAO(Food and Agriculture Organization) for the past 40 years of its establishment, its services to mankind, the hope vested on the Organization by its founders, the tides, endeavor, achievement among others.
asm; 30/10/2019.
Loans